Homework Help

Do you always use the property of distribution when multiplying monomials and...

user profile pic

smallsterea | (Level 1) Honors

Posted April 29, 2013 at 1:09 PM via web

dislike 2 like

Do you always use the property of distribution when multiplying monomials and polynomials? Explain. In what situations would distribution become important?

2 Answers | Add Yours

user profile pic

pramodpandey | College Teacher | (Level 3) Valedictorian

Posted April 29, 2013 at 1:21 PM (Answer #1)

dislike 2 like

Yes ,we always apply distribution property reason just see here

Let P(x) is polynomial and given as

`P(x)=2x^2+3x+1`

and Q(x) is monomial given as

`Q(x)=3x^2`

`So`

`Q(x)xx P(x)=3x^2 xx(2x^2+3x+1)`

`=3x^2 xx2x^2+3x^2 xx 3x+3x^2`

`=6x^4+9x^3+3x^2`

`` Distribution property is always important.

Take utmost care while removing brackets a,d minus sign.

 

user profile pic

oldnick | (Level 1) Valedictorian

Posted April 29, 2013 at 2:03 PM (Answer #2)

dislike 1 like

Yes the lonley case you havent to, is when multiply  two  monomials:

`2xy xx 3x^2y^3= 6x^3 y^4`

In other case  distribution rule is to be used:

`3x xx (5x+4y)= 3x xx 5x+ 3x xx 4y= 15x^2+ 12xy`

And more if you have to multiply two polinomials:

`(4x+3y)(7x+5y)= 4x xx 7x+ 4x xx 5y+ 3y xx 7x + 3y xx 5y=`

`=28x^2 +20xy+ 21xy +15y^2` `= 28x^2+41xy+15y^2`

Sometimes  it is useful to find to write the polynomial product in a convenient wayinstead to develope by distribution rule:`(x-1)(3x-1)+1=3x `

Supose you have to find solution of this:

Then you may develope it:

`3x^2-4x+1+1=3x`

`3x^2-4x+2=3x`

`3x^2-7x+2=0`

You have now a quadratic equation to solve that gives roots as:

`x_1=2`   and `x_2=1/3`

Now go back at initial equation:

`(x-1)(3x-1)+1=3x`

Inastead to develop product you can subtrac 1 both sides:

`(x-1)(3x-1)=3x-1`

Look! the factor  3x -1 is both sides  so if you bring it into left sides of equation:

`(x-1)(3x-1)-(3x-1)=0`

`(x-1)(3x-1) - 1xx (3x-1)=0`

Using inverse distribution rule you get:

`(x-1-1)(3x-1)=0`

`(x-2)(3x-1)=0`

Now a product is zero if and oly if  one or both terms of the product itself  are zero:

So the possible solution are :  `x_1=2`  and `x_2=1/3`

The same  we have find by solution of quadratic equation.

The difference is that in the second method we have solved  equation, without using second degreee method, more difficult.

Of course isn't always allowed to do this, but there isn't a  unic system to understand to act, but experience, and the more excercise to have a good look about. 

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes